Osteocranium of the Sailfish (Istiophorus platypterus, Shaw & Nodder, 1792) from Malacca Strait - Yusrizal Akmal; Mujibul Rahman; Muliari Muliari; Agung Setia Batubara (Universitas Gadjah Mada, 2022)
The features and morphometrics of the sailfish's osteocranium are examined in this study (Istiophorus platypterus, Shaw & Nodder, 1792). I. platypterus has a total weight of ±20 kg with a total length of ±218 cm. The stages of the research process included preparing samples, preparing osteocraniums, documenting photos, editing images, and identifying terminology related to osteocraniums. The Laboratory of Mathematics and Natural Sciences at Almuslim University handled every aspect of the research. The osteocranium preparation process was carried out physically and chemically. Each bone was documented using a camera and edited using Adobe Photoshop CS6. The neurocranium is divided into four components: the olfactory (ethmoidal), which comprises 6 bones. The orbitale comprises 4 bones, the otic comprises 5, and the occipital comprises 4 bones. The branchiocranium is divided into five components: the oromandibular structure consisting of 3 bones, the mandibular arc (suspensorium) composed of 4 bones, the opercular apparatus consisting of 4 bones, and the hyoid arc composed of 6 bones, and the branchial arc composed of 4 bones.